2003
DOI: 10.1029/2002jd002970
|View full text |Cite
|
Sign up to set email alerts
|

A modeling study of the stratospheric NOx/NOy and NOx/HNO3 ratios: Single‐ versus dual‐channeled mode of OH, NO2 association

Abstract: [1] UARS observations bearing upon the NO x /NO y and NO x /HNO 3 ratios were revisited within the framework of advances in laboratory studies that were spurred by the findings, around 1999, of considerable model underestimation of the observations. The objective was to study the two models of the OH, NO 2 association reaction, one that considers the single HNO 3 product channel and the other that considers dual HNO 3 and HOONO products channels. Rate coefficients of the OH + HNO 3 and the single-channeled OH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In particular for nitrogen gas-phase chemistry, revised kinetic data were recommended because, following a number of studies (e.g. Brown et al, 1999;Gao et al, 1999;Jucks et al, 1999;Osterman et al, 1999;Kondo et al, 2000;Prasad, 2003), a lower rate for the reaction of NO 2 with OH and a higher rate for HNO 3 with OH significantly reduced model-measurement discrepancies highlighted in former published work (e.g. Fahey et al, 1993;Kondo et al, 1997;Sen et al, 1998).…”
Section: Appendix B: Model Descriptionmentioning
confidence: 99%
“…In particular for nitrogen gas-phase chemistry, revised kinetic data were recommended because, following a number of studies (e.g. Brown et al, 1999;Gao et al, 1999;Jucks et al, 1999;Osterman et al, 1999;Kondo et al, 2000;Prasad, 2003), a lower rate for the reaction of NO 2 with OH and a higher rate for HNO 3 with OH significantly reduced model-measurement discrepancies highlighted in former published work (e.g. Fahey et al, 1993;Kondo et al, 1997;Sen et al, 1998).…”
Section: Appendix B: Model Descriptionmentioning
confidence: 99%
“…As a result, the amount of ozone-depleting NO x is strongly reduced (e.g. Prather, 1992;Johnston et al, 1992;Fahey et al, 1993;Mills et al, 1993;Solomon et al, 1994;Kondo et al, 1997;Sen et al, 1998;Dhomse et al, 2015), whereas HNO 3 amounts increase (Koike et al, 1993(Koike et al, , 1994Webster et al, 1994;Rinsland et al, 2003) as shown for the Pinatubo aerosols. Different chemical impacts on stratospheric ozone are expected depending on the altitude.…”
Section: Introductionmentioning
confidence: 89%
“…It results in the additional formation of HNO 3 on sulfate aerosols and in the formation of reactive chlorine in sunlight, where HOCl is rapidly photolysed releasing Cl radicals (e.g. Hofmann and Solomon, 1989;Prather, 1992;McElroy et al, 1992). This heterogeneous reaction is highly dependent on the water content in the aerosols and has been shown to be of considerable importance in determining the abundance of active chlorine available to destroy ozone under some conditions, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The present study followed the recommendations of JPL 00‐3 for the calculation of H 2 SO 4 wt% from temperature and the partial pressure of H 2 O, parameters for H 2 SO 4 solution and the uptake model parameters for ClONO 2 + H 2 O, ClONO 2 + HCl, HOCl + HCl reactions. This approach is the same as the approach taken by one of us [ Prasad , 2003a] in his study of the stratospheric NO X /NO Y and NO X /HNO 3 ratios. A useful comparison of the pre‐ and post‐ JPL00‐3 implementation of the reactions on sulfate aerosols can be found in that paper.…”
Section: Model Descriptionmentioning
confidence: 99%
“…According to the current understanding of the stratospheric NO X /NO Y chemistry, the theoretical models underestimate that ratio [ Danilin et al , 1999]. Although the newer experimental data and theoretical models of OH, NO 2 association and the HNO 3 + OH reaction [e.g., Donahue et al , 1997; Brown et al , 1999a, 1999b; Golden and Smith , 2000] produce a significant improvement, the problem persists [ Prasad , 2003a]. As pointed out earlier, the may not provide any reprieve in this matter, since the new source affect both NO X and NO Y similarly.…”
Section: Effects On the Current Understanding Of Atmospheric Nox‐noy mentioning
confidence: 99%